The Evolution of Media Culture Studies: A Comparative Bibliometric Approach Using Scopus and Web of Science (2000-2025) (Herald of Journalism, 2025)
This study presents a comprehensive bibliometric and content analysis of global research on media culture from 2000 to 2025, based on data retrieved from Scopus and Web of Science. Using the keyword "media culture", over 53,000 records were examined to identify publication trends, prolific authors, dominant disciplines, geographic distribution, document types, and thematic clusters.The methodology included quantitative aggregation, keyword co-occurrence mapping via VOSviewer, and theory-driven interpretation. Results showed a marked increase in research output after 2010, correlating with the rise of digital platforms and participatory media. Four key thematic areas were identified: (1) science communication and journalism, (2) health and crisis communication, (3) media effects and identity, and (4) social media and influencer culture. The field remains rooted in social sciences and humanities, yet reveals growing interdisciplinarity and contributions from the Global South and East Asia. The study provides a comprehensive knowledge map of media culture research and contributes to the theoretical and methodological advancement of media and communication studies. The findings confirm the hypothesis that media culture has evolved into a transdisciplinary field shaped by digital transformations and global shifts in journalism. This research lays a foundation for future empirical inquiries, policy-relevant media research, and theory development.
Keywords: Bibliometric analysis, media culture, Scopus, Web of Science, VOSviewer.